Exploring the Evolution of Qualitative Methodologies in Islamic Education Research: A 25-Year Bibliometric Review from Scopus (2000–2025) - Eko Ngabdul Shodikin; Naila Intania; Mansur Mansur; Fais Maftuch (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study analyzes the development of Islamic Religious Education (IRE) research from 2000 to 2025 using a bibliometric approach based on Scopus-indexed publications. Through this analysis, the study maps the dynamics of scientific production, including publication trends, leading authors, institutions, countries, influential journals, as well as thematic patterns and collaboration networks within qualitative IRE research. A total of 1,023 articles were examined using VOSviewer and the Bibliometrix R-package to generate visualizations of knowledge structures, author collaborations, and keyword evolution. The findings reveal a substantial increase in publication volume during the last decade, accompanied by a methodological transition from normative–doctrinal approaches to phenomenological, interpretive, and ethnographic frameworks. Dominant research themes include religious moderation, character education, and the integration of Islamic values in pedagogical practices. Indonesia, Malaysia, and Saudi Arabia emerge as the major contributors to qualitative IRE literature, reflecting their strong academic engagement in the field. The novelty of this study lies in its comprehensive quantitative and visual mapping of the scientific landscape of IRE, offering the first systematic overview of how qualitative methodologies in IRE have evolved over the past 25 years. The main contribution of this research is the provision of a bibliometric map that can guide future research agendas, support the development of methodology-focused curricula, and strengthen international academic collaboration in Islamic education. The findings also carry practical implications for policymakers, offering evidence-based insights for designing initiatives that promote quality enhancement in Islamic education research and practice.